Comparison of different modified operations in the reduced uteroplacental perfusion pressure rat model of preeclampsia. (March 2023) - Shi, Meiting; Yang, Xiaofeng; Sun, Lu; Ding, Yuzhen; Huang, Zhengrui; Zhang, Ping; Yang, Xuesong; Li, Ruiman; Wang, Guang
Abstract: Introduction: Animal models are indispensable tools in studying the mechanisms underlying the diseases. Rat models with reduced uterine perfusion pressure (RUPP) were able to mimic the pathophysiological traits of placental ischemia and hypoxia in preeclampsia (PE). However, ischemic injury can lead to a cascade of damage to lower limb ischemia in RUPP. Therefore, the aim of our study was to compare three modified surgical procedures of reducing uteroplacental perfusion pressure, and to provide a reference for the recognition of different PE phenotypes in the future. Material and methods: To establish a specific uteroplacental malperfusion model of PE in rats, we bilaterally ligated uterine vessels (UU), ovarian vessels distal to ovarian branches (OO), or both (sRUPP) at 13.5 days post coitum. 21 Sprague-Dawley rats in total were used and were divided into four groups: Sham (n = 4), UU (n = 6), OO (n = 5) and sRUPP (n = 8). Results: The results showed that the OO and sRUPP groups could successfully mimic the phenotypes of PE while UU group not. Then, autophagy, apoptosis, and synthesis of unsaturated fatty acids were increased in both the OO and sRUPP groups compared with the Sham group, while inflammation were not statistically different. Conclusions: The OO and sRUPP groups could successfully establish the rat model of PE while the UU group not. Notably, between the OO and sRUPP groups, the OO group has a higher fetal survival rate and might be more suitable for studying fetal-related questions, while the sRUPP group has a heavier phenotypic profile and is more suitable for studying maternal phenotypes related to PE. Highlights: Compared different modified operations in Reduced Uteroplacental Perfusion Rat. Both OO and sRUPP could successfully mimic the phenotypes of preeslampsia. Autophagy and apoptosis were increased in both the OO and sRUPP group. The OO group might be more suitable for studying fetal-related questions. The sRUPP group might be more suitable for studying PE maternal phenotypes.